Factors affecting the market supply value chain of apricot in Kandahar, Afghanistan - Hashimi, Sardar Mohammad (2020)
Apricot (Prunus armeniaca) is the fourth most important perennial crop that has considerably amplified the country’s profile, particularly in the production of horticultural crops. However, the contribution of Afghan apricot has been observed with declining trend in the recent years. This study focused on the factors affecting the market supply value chain of apricot in Kandahar, Afghanistan. The specific objectives in the present study were i) to map the value chain and marketing channels of apricots used by the supply chain players, ii) to identify the production and marketing constraints faced by the apricot farmers, iii) to explore the association between socio-demographic profile and quantity of apricot supplied to the market, and iv) to determine the most influential factors affecting quantity of apricot supply to the market. A cross-sectional study design was adopted in this study. A wellstructured close ended questionnaire via face to face survey was used to collect primary data from 102 farmers, 15 wholesalers, 25 retailers, 5 processors, 10 collectors and 10 exporters. Descriptive statistics were used to identify the constraints and mapping value chain and marketing channels used by the supply chain actors. Chi-square analysis was performed to explore the association between socio-demographic profile and quantity of apricot supplied. Factors influencing apricot supply were identified using factor analysis, while multiple regression analysis was performed to determine the most influential factors influencing apricot supply. Descriptive statistics showed that the chain was constrained by drought, diseases, shortage of land, poor extension services, lack of credit, high inputs price and lack of fertilizers, lack of storage, poor governance of the chain, poor quality of the apricot, lack of supply, high transport cost and lack of demand. The results also indicated that the main actors in apricot supply chain include input suppliers, farmers/processors, wholesalers, collectors, retailers, and exporters. Chi-square test showed that farm size, education level and farming experience are associated with quantity of apricot supplied. Factor analysis revealed seven (7) underlying factors namely, storage availability, market and variety information, access to credit, cost minimization, logistical efficiency, price awareness and extension services. These factors were able to explain 82.135% of the variance in the analysis. Multiple regression analysis indicated that apricot quantity supplied was influenced significantly by storage availability, logistical efficiency, price awareness, extension services and farm size at the level of 1%, 1%, 1%, 5% and 1%, respectively. It can be concluded that apricot is cultivated by smallholder farmers and the production is managed by young farmers. The marketing channels were mostly controlled by wholesalers. Findings of this study suggest that there is the need for designing appropriate intervention mechanisms focusing abovementioned factors to improve the chain and raise apricot smallholder farmers in Kandahar, Afghanistan.